A Macrophage Differentiation-Mediated Gene: DDX20 as a Molecular Biomarker Encompassing the Tumor Microenvironment, Disease Staging, and Prognoses in Hepatocellular Carcinoma. (5th October 2022) - Yang, Yi; Yang, Ming; Pang, Huasheng; Qiu, Yiwen; Sun, Ting; Wang, Tao; Shen, Shu; Wang, Wentao
Abstract : Background . DDX20 involves the mechanism of cell proliferate, mitogenic Ets transcriptional suppressor (METS), which can arrest the cell cycle of macrophages. However, little is known about DDX20 expression, clinical values, and the relationship with tumor microenvironment in HCC. Methods . We mined the transcriptional, protein expression and survival data of DDX20 in HCC from online databases. The immunological effects of DDX20 were estimated by bioinformatic algorithms. The RNAi and CRISPR screening were used to assess the gene effect of DDX20 for the EGFR gene in liver tumor cell. Results . We found that the DDX20 was highly expressed in HCC. The qRT-PCR result shows a significantly upregulated DDX20 expression in HCC samples from the West China Hospital. The high mRNA expression of DDX20 is associated with a poor survival. DDX20 expression is positively correlated with MDSCs in HCC tissues. Moreover, DDX20 has a high predicted ability for the response to immunotherapy. Furthermore, hsa-mir-324-5p could regulate the macrophage differentiation by interacting with DDX20. Meanwhile, the EGFR gene gets a high dependency score for DDX20. Conclusion . In sum, DDX20 may serve as a prognostic marker for worse clinical outcomes with HCC and potentially enable more precise and personalized immunotherapeutic strategies in the future.